Efektivitas Tugas Dan Fungsi Satuan Polisi Pamong Praja Dalam Meningkatkan Ketertiban Umum Di Kota Pekanbaru - YASMI, MUHAMMAD ARIF; ", SUJIANTO (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
A civil service police unit officers who helped to create a regional head of local conditions is peaceful , orderly and organized so that the implementation of the government to run smoothly. But in fact every right the situation and attitude always gave the impression of violence, even civil service police unit officers who conduct illegal fees on society, as well as in carrying out police force policing the civil service tend not to put forward a persuasive approach, but tend to use violence. based on these phenomena, the formulation of the problem in this research is how the effectiveness of the duties and functions of the civil service police force in improving public order in the city of Pekanbaru. Purpose of the study to determine the effectiveness of the duties and functions of the civil service police force in the city of Pekanbaru improve public order and to determine the factors that influence the effectiveness of the duties and functions of the civil service police force in improving public order in the city of PekanbaruResearch methods used in this study is a quantitative and qualitative. By taking a descriptive research, in this study collection techniques used are observation, interviews, and questionnaires. So the effectiveness of the duties and functions of Satpol PP in improving public order in the city of Pekanbaru be known. In this study the authors only take a sample of 40 people from the 185 number Satpol PP officers, other than that in order to comparison with the aim of obtaining information that is not biased and inaccurate samples, the authors add people or street vendors pekanbaru town of 10 people from the amount that is not infinity by incidental sampling.Based on research in the field that the effectiveness of the duties and functions of Satpol PP in improving public order in the city of Pekanbaru done pretty well. Respondents thought that the Satpol PP officers in the duties and functions of the effectiveness in improving public order in the city of Pekanbaru is quite capable of doing a good job. As for the factors that are affecting the state of Satpol PP officers and community participation.Keywords: Effectiveness, Duties and Functions, and Public Order